Efficacy of Curry Leaf Powder and Tomato Paste on Storage Stability of Chicken Meat Patties - Reddy, B. Obula; Rao, B. Eswara; Mallika, E. Naga; Rao, T. Srinivasa; Reddy , G.V. Bhaskar (Journal of Meat Science, 2015)
A study was conducted to investigate the effect natural antioxidants i.e. of curry leaf powder and tomato paste comparing with synthetic antioxidant (butylated hydroxyl anisole) on the quality and storage stability of chicken meat patties added with 5 per cent oat flour at refrigeration (4±1°C) temperature. Storage studies revealed a significant (p
Keywords: Lipid oxidation; Oat flour; Curry leaf power; Tomato paste; Storage stability